Clinician perception of pathological narcissism in females: a vignette-based study - Green, Ava; MacLean, Rory; Charles, Kathy (Frontiers in Psychology, 2023)
The DSM-5 reports that up to 75% of those diagnosed with Narcissistic Personality Disorder (NPD) are males, which denotes that narcissism is a clinical phenomenon that operates differently in men and women. Vulnerable narcissism, which tends to be more prevalent in females and is currently under-appreciated in the DSM-5, may be diagnosed as other ‘vulnerable’ disorders (e.g., Borderline Personality Disorder; BPD). The current study investigated gender differences in clinicians’ perceptions of narcissistic pathology. Adopting an online vignette-based study, clinicians (N = 108; 79 females) read clinical case vignettes of hypothetical patients and provided diagnostic ratings of existing personality disorders. Clinicians’ diagnostic ratings of NPD were concurrent with the vignette containing grandiose narcissism symptoms, irrespective of patient gender. However, when presented with a vulnerable narcissism vignette, clinicians were significantly more likely to attribute a BPD diagnosis in female patients, compared to male patients. Clinicians with a psychotherapeutic approach and more experience in practice were also more likely to label vulnerable narcissism symptoms as NPD, compared to those with a CBT approach and less experience in practice. The clinical implications of these results support the shift towards assessing personality dysfunction based on dimensional trait domains.